Vacancies and residential search in an empirical equilibrium search model - Arno J. van der Vlist; Cees Gorter; Piet Rietveld; Peter Nijkamp (European Regional Science Association (ERSA), 1998)
As is well known housing has a unique set of characteristics which interact to cause the operation of the housing market to be significantly different from that of other markets. On the demand side individuals have to search for vacancies and its characteristics. Due to the high dimensionality of housing considerable search costs are involved. On the supply side, complicated interactions exist in the housing market whereby frictions occur frequently. In the labour market similar behaviour has been explained with search and matching models, where vacancies and turnovers are explicitly considered. Wheaton (1990) remarks that these search and matching models from the labour market would seem particularly applicable to housing. In this paper we formulate an equilibrium search model of the housing market that deals with search and prices. We beleive that an equilibrium searchmodel could be an important step forward into the analysis of vacancies and residential search. Using this framework we formulate an empirical model for the Dutch housing market.
Keywords: 330